Solitary fibrous tumor of the prostate: a case report and the systematic review of 74 published cases - Zhang, Hang; Yan, Chunyue; Zhang, Daowen; Chen, Zhipeng; Wang, Kun; Zhou, Fan; Yang, Ming; Wang, Fei (Frontiers in Oncology, 2025)
PurposeThis study aimed to report a rare case of solitary fibrous tumor of prostate (pSFT) and achieve the first systematic review of 74 published pSFT cases, and to integrate the end-to-end management of pSFT from preoperative diagnosis, treatment, and follow-up.Methods and case reportThis study reports a additional case of pSFT. Subsequently, we performed a systematic review of PubMed, Web of Science, Cochrane Library, and Embase databases for potentially relevant articles on pSFT from inception of database to October 2024. Two researchers independently screened eligible literature, extracted data, and summarized data.ResultsA 71-year-old male patient presented to our hospital with a three-month history of dysuria, and prostate-specific antigen (PSA) was within the normal range. After transurethral prostatectomy, the histopathological diagnosis was pSFT. During three years of outpatient follow-up, the patient had no recurrence. Ultimately, forty literatures were included with 74 cases of pSFT, and age ranged from 21 to 89 years (mean 57.5 years, median 61.5 years). There were 42 cases (56.8%) in North America, 22 cases (29.7%) in Asia, 9 cases (12.2%) in Europe, and 1 case (1.4%) in Oceania. The PSA values were within the normal range in almost all cases, and about 47.3% (35/74) cases underwent ultrasound, magnetic resonance imaging or CT examination before surgery. Notably, the most characteristic imaging biomarkers of the tumor were continuous and gradual enhancement from the periphery to the center with visible separation and capsule. The malignancy rate was 21.6% (16/74). There was no significant difference between benign and malignant pSFT of the lesion size (P > 0.05). Meanwhile, STAT6 and/or NAB2-STAT6 fusion genes were very sensitive biomarkers for pSFT. The median follow-up time of 38 patients with pSFT was 18 months (2–168 months), and the disease-free survival of benign, borderline and malignant pSFT was statistically significant (P=0.011).ConclusionsThis study presents a new case and provides the first systematic review for 74 cases of pSFT, integrating clinical presentation, pathology, imaging, and follow-up data to assist surgeons in surgical planning. Surgical resection is the preferred treatment for pSFT, and regular follow-up is of vital importance. Due to the heterogeneity among current studies, future research may require standardized data reports and the establishment of a homogeneous public database to prepare for subsequent pSFT risk stratification studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251004804.